Electrocardiography in Post-heart Transplant - Neda Toofaninejad (Publisher: Shahid Beheshti University of Medical Sciences, 2019)
The current study described the electrocardiography case of a 22-year-old male, a few months after heart transplantation that demonstrated two sets of QRS leading to understand the technique of the transplantation.